2001
DOI: 10.1258/1357633011936453
|View full text |Cite
|
Sign up to set email alerts
|

A cost-minimization analysis of the societal costs of realtime teledermatology compared with conventional care: results from a randomized controlled trial in New Zealand

Abstract: A randomized controlled trial was carried out to measure the societal costs of realtime teledermatology compared with those of conventional hospital care in New Zealand. Two rural health centres were linked to a specialist hospital via ISDN at 128 kbit/s. Over 10 months, 203 patients were referred for a specialist dermatological consultation and 26 were followed up, giving a total of 229 consultations. Fifty-four per cent were randomized to the teledermatology consultation and 46% to the conventional hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 10 publications
1
50
0
Order By: Relevance
“…Cost data were reported in 3 studies involving SAF teledermatology, 72-74 6 studies of LI teledermatology, 69,70,[75][76][77][78] and one study that included both SAF and LI teledermatology 79 (Table X; available online at http://www.eblue.org). Because of differences in factors included in cost assessments and the various perspectives (societal, health service, or patient), it was difficult to summarize these findings.…”
Section: Question 4: Costmentioning
confidence: 99%
“…Cost data were reported in 3 studies involving SAF teledermatology, 72-74 6 studies of LI teledermatology, 69,70,[75][76][77][78] and one study that included both SAF and LI teledermatology 79 (Table X; available online at http://www.eblue.org). Because of differences in factors included in cost assessments and the various perspectives (societal, health service, or patient), it was difficult to summarize these findings.…”
Section: Question 4: Costmentioning
confidence: 99%
“…For example, researchers in New Zealand found that, compared to a clinic visit, the use of LI teledermatology saved patients an average of 3.45 hours of time, primarily due to reduced traveling time (Oakley et al, 2000). However, LI teledermatology does not necessarily reduce consult time for the dermatologist (Loane et al, 1999(Loane et al, , 2001bOakley et al, 2000).…”
Section: Clinical Outcomes For LI Teledermatologymentioning
confidence: 99%
“…While some studies have shown LI teledermatology to be cost-effective, others suggested that it may be more costly than conventional care. In a cost-minimization analysis from a societal perspective, authors from New Zealand found that teledermatology consultations using LI technology appeared less costly than that of face-to-face care, especially when patients have longer travel distances (Loane et al, 2001b). In another costminimization study of LI teledermatology in the U.S., investigators found that consultative teledermatology using LI technology also appears to be less costly than face-to-face care from a provider perspective (Armstrong et al, 2007).…”
Section: Economic Considerations Of Live Interactive Teledermatologymentioning
confidence: 99%
“…From a societal viewpoint, and assuming an equal outcome, teledermatology seems to be a more cost-effective use of resources than conventional hospital care [6]. …”
Section: Technologymentioning
confidence: 99%